Evaluasi Pendidikan Perspektif Islam dan Barat: : Framework Integratif - Latifatuzzahra; Shiddiqa Saelan Mumpuni; Dwi Meutia Hasni (ASSUNNAH PRESS, 2025)
The evaluation of Islamic education emphasizes the formation of character, spirituality, and the internalization of values, and norms. Meanwhile, the evaluation approach in the Western tradition focuses on the systematics of an educational program, the objectivity, quantitativeness, and final results of a program. This research aims to integrate these two approaches by developing an integrative framework that is comprehensive and contextual. This research is based on a qualitative methodology with a library research approach, which is to review previous literature that is in line with the topic of this study. The results obtained show that the concept of evaluating Islamic and Western perspectives has fundamental differences, but they are complementary to each other, therefore the author develops an integrative framework based on Islamic and Western evaluation models. The novelty of this research lies in the effort to unite the two evaluation paradigms to produce a model that is transformative, applicative, and by the needs of contemporary Islamic educational institutions. This research is expected to be a reference for Islamic educational institutions, which are contextual with the times, but still maintain their Islamic identity.